Respuesta :

4b + 3s = 11.93 ⇒ 4b + 3s = 11.93
2b + 2s =   6.76 ⇒ 4b + 4s = 13.52
                                       -s = -1.59
                                        s = 1.59
                              2b + 2s = 6.76
                       2b + 2(1.59) = 6.76
                           2b + 3.18 = 6.76
                                 - 3.18  - 3.18
                                       2b = 3.58
                                        2        2
                                         b = 1.79
                                   (b, s) = (1.79, 1.59)